Multiple Sclerosis in the Emirati Population: Onset Disease Characterization by MR Imaging. (25th November 2019) - Ahmed, Manzoor; Mir, Ruqqiya; Shakra, Mustafa; Al Fardan, Safana
Abstract : Background and Objectives . Multiple Sclerosis (MS) epidemiology is on the path of globalization mainly due to changing environmental factors. The prevalence of MS is on the rise in the Middle East and Persian Gulf region. Our observations has led us to hypothesize a heavy MRI lesion load at the onset of disease in a relatively younger native population. We aimed to estimate and characterize the onset disease on MRI using McDonald's criteria while applying its terms of "Dissemination in Space (DIS) and Dissemination in Time (DIT)". Materials and Methods . Retrospective review of onset MRI studies of 181 Emirati (native) individuals. Basic demographics were captured. Only 47 patients with Clinically Definite MS (CDMS) were included who had onset diagnostic MRI available. Lesion load was quantified using the specific zones of involvement designated for DIS: (1) Periventricular (PVZ) (I), (2) Juxta-cortical (II) (3) Infra-tentorial (III) and, (4) Spinal cord (IV). PVZ was sub-classified and lesions were quantified. A single enhancing lesion was required for DIT. Results . Average age of onset was about 26 years with female dominance of about 2 : 1. About 50% had all 4 zones and about 85% had at least 3 zones involved at the onset. Involvement of only 1 zone was rare. Dissemination in time (DIT) in brain and/or cord was present in approximately 50%. Each of the 4 zones were involved in at least 70% of cases. PVZ was not spared in any case with at least 3 lesions present in approx. 95% and ≥12 lesions in approx. half of the patients. Spinal cord specifically cervical cord was involved in up to 80% with typical patchy lesions. Conclusion . Onset disease characterization using MRI in a young Emirati cohort showed a heavy lesion load in the brain and spinal cord at the onset, signifying cumulative disease before presentation. Disseminated disease also facilitated early diagnosis of MS. The findings have significant potential ramifications for local environmental and cultural factors, as well as disease course and disability progression.